Elevated IgG4 in patient circulation is associated with the risk of disease progression in melanoma - Karagiannis, Panagiotis (Oncoimmunology, 2015)
Emerging evidence suggests pathological and immunoregulatory functions for IgG4 antibodies and IgG4(+) B cells in inflammatory diseases and malignancies. We previously reported that IgG4 antibodies restrict activation of immune effector cell functions and impair humoral responses in melanoma. Here, we investigate IgG4 as a predictor of risk for disease progression in a study of human sera (n = 271: 167 melanoma patients; 104 healthy volunteers) and peripheral blood B cells (n = 71: 47 melanoma patients; 24 healthy volunteers). IgG4 (IgG4/IgG(total)) serum levels were elevated in melanoma. High relative IgG4 levels negatively correlated with progression-free survival (PFS) and overall survival. In early stage (I–II) disease, serum IgG4 was independently negatively prognostic for progression-free survival, as was elevation of IgG4(+) circulating B cells (CD45(+)CD22(+)CD19(+)CD3(−)CD14(−)). In human tissues (n = 256; 108 cutaneous melanomas; 56 involved lymph nodes; 60 distant metastases; 32 normal skin samples) IgG4(+) cell infiltrates were found in 42.6% of melanomas, 21.4% of involved lymph nodes and 30% of metastases, suggesting inflammatory conditions that favor IgG4 at the peripheral and local levels. Consistent with emerging evidence for an immunosuppressive role for IgG4, these findings indicate association of elevated IgG4 with disease progression and less favorable clinical outcomes. Characterizing immunoglobulin and other humoral immune profiles in melanoma might identify valuable prognostic tools for patient stratification and in the future lead to more effective treatments less prone to tumor-induced blockade mechanisms.